STRATEGI GURU DALAM MENSTIMULASI LIFE SKILL ANAK USIA DINI DI TK AN- NAHL PERCIKAN IMAN UNIVERSITAS JAMBI - Isshaleha, Indah; Hasni, Uswatul; Amanda, Rizki Surya (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe and understand in depth the strategies of teachers in stimulating life skills in early childhood. This study uses a qualitative approach with a phenomenological method, which aims to uncover the meaning and direct experiences of teachers in designing and implementing various learning strategies oriented towards the development of life skills in early childhood. The subjects of the study were teachers who teach in early childhood education institutions. Data collection was carried out through in-depth interviews, participant observation, and documentation. Data analysis used the stages of reduction, description, and interpretation of phenomena based on the lived experiences of informants. The results of the study show that the strategies used in An-Nahl Kindergarten use 4 stages: planning, organizing, implementation, and evaluation/monitoring. These 4 components run in a structured and systematic manner, including: planning in the form of compiling programs and objectives according to children's needs; organizing, namely the preparation of teaching staff and structuring the learning environment; implementation, namely the direct application of all stimulation methods and activities integrated into learning; and finally, evaluation, namely continuous assessment as a basis for improving subsequent strategies.